Analysis of Illocutionary Speech Acts in the "Independent Curriculum" Playlist on the Learning Friends Channel - Alfina Nur Azizah; Nela Nafisah; Izza Safira Amalia; Ummi Mulyaningsih; Nazha Alyandra Ferdiansyah; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (International Journal of Educational Technology and Society, 2024)
The research entitled Analysis of Illocutionary Speech Acts in the "Independence Curriculum" Playlist in the Friends of Learners Channel is motivated by the presence of interesting words to analyze and aims to describe illocutionary speech acts in speakers' speeches. This research is to explain illocutionary speech acts in the “Independence Curriculum” playlist on the Friends of Learners channel. This study uses a qualitative description method, the data source is from the "Independence Curriculum" playlist on the Friends of Learners Channel on YouTube social media. The data in this study are speech transcripts in the form of sentences or paragraphs indicating the existence of illocutionary speech acts in the "Independence Curriculum" playlist on the Friends of Learners Channel. The data collection technique is the listening and note-taking technique. The results showed that there were various types of illocutionary speech acts. Based on the results of research on illocutionary speech acts in the "Independence Curriculum" playlist on the Friends of Learners Channel, 15 illocutionary speech acts were found which included: 3 assertive speech acts, 3 declarative speech acts, 3 directive speech acts, 4 commissive speech acts, 2 expressive speech acts. The benefit of this research is that we can find out speech acts and as a reference in language in society.